2022
DOI: 10.3390/nano12122022
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pulmonary Toxicity in Metabolic Syndrome Due to Variations in Iron Oxide Nanoparticle-Biocorona Composition

Abstract: Nanoparticles (NPs) interact with biomolecules by forming a biocorona (BC) on their surface after introduction into the body and alter cell interactions and toxicity. Metabolic syndrome (MetS) is a prevalent condition and enhances susceptibility to inhaled exposures. We hypothesize that distinct NP-biomolecule interactions occur in the lungs due to MetS resulting in the formation of unique NP-BCs contributing to enhanced toxicity. Bronchoalveolar lavage fluid (BALF) was collected from healthy and MetS mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…Achieving this goal would empower toxicologists to accurately detect NPs in biological systems, facilitate the establishment of clear standards, and enable the proactive notification of those at high risk of exposure. For instance, epidemiological and murine studies have suggested that individuals with pre-existing conditions, such as Frontiers in Toxicology frontiersin.org metabolic syndromes, are more susceptible to engineered nanoparticles' impact than healthier individuals (Kobos et al, 2019;Alqahtani et al, 2020;Kobos et al, 2020;Alqahtani et al, 2021;Alqahtani et al, 2022;Xia et al, 2022). Similar vulnerabilities may well extend to the exposure to NPs.…”
Section: Detection Of Microplastics and Nanoplasticsmentioning
confidence: 99%
“…Achieving this goal would empower toxicologists to accurately detect NPs in biological systems, facilitate the establishment of clear standards, and enable the proactive notification of those at high risk of exposure. For instance, epidemiological and murine studies have suggested that individuals with pre-existing conditions, such as Frontiers in Toxicology frontiersin.org metabolic syndromes, are more susceptible to engineered nanoparticles' impact than healthier individuals (Kobos et al, 2019;Alqahtani et al, 2020;Kobos et al, 2020;Alqahtani et al, 2021;Alqahtani et al, 2022;Xia et al, 2022). Similar vulnerabilities may well extend to the exposure to NPs.…”
Section: Detection Of Microplastics and Nanoplasticsmentioning
confidence: 99%